The Moderating Role Of Good Corporate Governance In The Relationship Between Green Innovation, Environmental Disclosure And Firm Value - Samhadi; Roekhudin; Syaiful Iqbal (Universitas Muhammadiyah Malang, 2024)
Purpose: This research examines and analyses the effect of green innovation and environmental disclosure on firm value. This study also adds the role of good corporate governance as a moderating variable on the relationship between green innovation and environmental disclosure with firm value. Methodology/approach: This research uses an explanatory method with a quantitative approach. Findings: The results of this study indicate that environmental disclosure has a positive effect on firm value, while green innovation has no effect on firm value. Furthermore, the results of the moderation regression analysis show that the role of good governance can strengthen the relationship between green innovation and environmental disclosure with firm value. Practical implications: This research is expected to be a consideration for investors so that companies can implement good corporate governance through green innovation and environmental disclosure as a form of concern for the environment and sustainability. Originality/value: This study adds the moderating variable of good corporate governance, which is thought to have a combined influence in the relationship between green innovation and environmental disclosure on firm value which aims to answer the inconsistency of previous research findings. This study also uses a research sample with the latest year, thus providing research results that are relevant to current conditions.